Identifying auditory cortex encoding abnormalities in schizophrenia: The utility of low‐frequency versus 40 Hz steady‐state measures. (23rd March 2018) - Edgar, J. C.; Fisk, Charles L.; Chen, Yu‐Han; Stone‐Howell, Breannan; Liu, Song; Hunter, Michael A.; Huang, Mingxiong; Bustillo, Juan; Cañive, José M.; Miller, Gregory A.
Abstract: Magnetoencephalography (MEG) and EEG have identified poststimulus low frequency and 40 Hz steady‐state auditory encoding abnormalities in schizophrenia (SZ). Negative findings have also appeared. To identify factors contributing to these inconsistencies, healthy control (HC) and SZ group differences were examined in MEG and EEG source space and EEG sensor space, with better group differentiation hypothesized for source than sensor measures given greater predictive utility for source measures. Fifty‐five HC and 41 chronic SZ were presented 500 Hz sinusoidal stimuli modulated at 40 Hz during simultaneous whole‐head MEG and EEG. MEG and EEG source models using left and right superior temporal gyrus (STG) dipoles estimated trial‐to‐trial phase similarity and percent change from prestimulus baseline. Group differences in poststimulus low‐frequency activity and 40 Hz steady‐state response were evaluated. Several EEG sensor analysis strategies were also examined. Poststimulus low‐frequency group differences were observed across all methods. Given an age‐related decrease in left STG 40 Hz steady‐state activity in HC (HC > SZ), 40 Hz steady‐state group differences were evident only in younger participants' source measures. Findings thus indicated that optimal data collection and analysis methods depend on the auditory encoding measure of interest. In addition, whereas results indicated that HC and SZ auditory encoding low‐frequency group differences are generally comparable across modality and analysis strategy (and thus not dependent on obtaining construct‐valid measures of left and right auditory cortex activity), 40 Hz steady‐state group‐difference findings are much more dependent on analysis strategy, with 40 Hz steady‐state source‐space findings providing the best group differentiation.